Mesoporous Zeolitic Materials (MZMs) Derived From Zeolite Y Using a Microwave Method for Catalysis - Abdulridha, Samer; Jiao, Yilai; Xu, Shaojun; Zhang, Rongxin; Garforth, Arthur A.; Fan, Xiaolei (Frontiers in Chemistry, 2020)
Mesostructured zeolitic materials (MZMs) with relatively high acidity in comparison with the mesoporous siliceous MCM-41 were prepared via an efficient, mild, and simple post-synthetic treatment of Y zeolite facilitated by microwave irradiation, i.e., microwave-assisted chelation (MWAC). The disordered mesoporous aluminosilicates materials (DMASs) of MZM were created from Y zeolite in the absence of using mesoscale templates. The prepared DMASs showed the good mesoporous features with the mesopore area and volume of ~260 m2 g−1 and ~0.37 cm3 g−1, respectively, and with the mesopore sizes distributed in a range of 2–10 nm. MZMs possess a total acidity of about 0.6 mmol g−1 and exhibited comparatively superior catalytic activity to the parent Y zeolite and MCM-41 in the vapor phase catalytic dealkylation of 1,3,5-triisopropylbenzene (TiPBz) and liquid phase catalytic aldol condensation of benzaldehyde with 1-heptanal. Although the yield loss was inevitable for preparing MZMs using the MWAC method, the preliminary economic analysis of the preparation cost of MZMs showed the promise. Additionally, a comprehensive comparison of the state-of-the-art mesoporous materials concerning their sustainable aspects was made, showing that MZMs are promising mesoporous materials for further development and functionalization for catalysis.